Human Resources Management – A Strategic Key towards Public Hospital Performance - Yasmin A. MOBASHER (Revista de Management Comparat International, 2022)
Improving patient care has become a priority for all healthcare providers, with the overall goal of achieving a high degree of patient satisfaction. The quality of patient care is essentially determined by the quality of the infrastructure, the quality of training, the competence of the staff and the efficiency of the operating systems. Staff constraints often compromise the quality of care. This can be corrected by introducing efficient and coherent human resources management policies. The capacity of hospitals to provide quality health care to all patients is based on competence, work and commitment. The medical challenges of recent years make it necessary to renew the approach to human resources management, seen as a major factor in organizational performance. The paper aims to analyse from a theoretical point of view the management of human resources as the main factor of increasing the performance of public hospitals. The article analyses the challenges of human resources management, the strategic management of human resources, the particularities of hospital services, the satisfaction and motivation of employees at the hospital workplace. Finally, a series of findings on the issue addressed are presented, highlighting a series of challenges on modernizing human resources policy in public hospitals.